Theoretical calculations of base-base interactions in nucleic acids: II. Stacking interactions in polynucleotides. - Gupta, G (1978)
Base-base interactions were computed for single- and double stranded poly,ucleotides, for all possible base sequences. In each case, both right and left stacking arrangements are energetically possible. The preference of one over the other depends upon the base-sequence and the orientation of the bases with respect to helix-axis. Inverted stacking arrangement is also energetically possible for both single- and double-stranded polynucleotides. Finally, interacting energies of a regular duplex and the alternative structures were compared. It was found that the type II model is energetically more favourable than the rest.